Evaluasi Kinerja Layanan Perpustakaan Digital Elfan Bookles Library di Kabupaten Sinjai - Mulia, Muh. Abrar; Sani, Kiki Rasmala; Nurdin, Mochamat (Literatify: Trends in Library Developments, 2026)
The rapid development of information technology has encouraged public libraries to transform into digital-based services. The Library and Archives Office of Sinjai Regency introduced the Elfan Bookles Library application in 2020 to expand access to digital collections; however, its utilization rate remains low. This study aims to evaluate the optimization of the digital library service at the local government level. This research employed a descriptive qualitative approach. Data were collected through interviews, observation, and document analysis involving purposively selected informants, including the head of the office, librarians, and digital library users. Data were analyzed using Miles and Huberman’s interactive model, guided by Gibson’s organizational effectiveness framework, which emphasizes effectiveness, efficiency, and productivity as key performance indicators.The findings indicate a 36.1% decline in application users over the past two years, despite fluctuating physical visitor numbers. Promotional efforts through social media and banners have not been consistently implemented, and the digital collection remains limited and unevenly distributed. These conditions contribute to low user engagement and limited service productivity. The study underscores the need for improved promotional strategies, diversification of digital collections, and continuous technical enhancement to achieve optimal service performance.This research contributes to the application of organizational effectiveness theory in evaluating digital library services at the local government level.